Literary Historiography of Dr. Jamil Jalbi - Ahmad Wali; Dr. Badshah Munir Bukhari (Zaban-o-Adab, 2021)
Dr. Jamil Jalibi’s "Tareekh Adab Urdu" is recognized as a work of basic reference among the literary histories of Urdu. He is a research oriented historian. He is, therefore, adept in logical and intellectual analysis. While finding the realities he tries his best to dig out the primary and secondary sources. One of the prominent features of this historical work is its amalgamation of both history and criticism which makes this historical work as an exquisite creation. The foundation of literary history writing laid by Dr. Jamil Jalibi is not based on what others say. He tried to touch the very soul of literature by directly benefiting from all the writings, works and almost all genuine historical and literary sources and has been perfectly successful.